Biodiversity of hillstream fishes in Bangladesh - Ahmed, Abu Tweb Abu; Rahman, Md. Mizanur; Mandal, Suman (Zootaxa, 2013)
Bangladesh is a country of 1,47,570 km2 of mostly flat topography, but about 12 percent is hilly. The hilly areas are confined to the northeast and the southeastern parts of the country bordering India and Myanmar. Hill streams are highly variable and very important for the study and understanding of the aquatic biodiversity of Bangladesh. Hillstream ecosystems include a variety of habitats including those with sand, clay, cobble, gravel, mud, and rock substrates. In a recent field survey, 82 species of fishes have been identified from those habitats. The ichthyofauna belongs to the following families (numbers of species in parentheses) Notopteridae (1), Engraulidae (1), Cyprinidae (32), Psilorhynchidae (3), Nemacheilidae (2), Cobitidae (6), Bagridae (6), Schilbeidae (5), Amblycipitidae (1), Akysidae (1), Sisoridae (4), Erethistidae (1), Clariidae (1), Olyridae (1), Aplocheilidae (1), Ambassidae (2), Badidae (1), Mugilidae (1), Gobiidae (2), Osphronemidae (2), Channidae (3), Mastacembelidae (3), Belonidae (1) and Tetraodontidae (1). This paper provides a checklist of the hillstream fish species with their habitat preferences and associated fauna.